Sensory Difficulties : Identifying and supporting needs, activities covering early learning goals, working with parents - Mortimer, Hannah (Leamington Spa : Scholastic, 2002)
This title provides help for practitioners on how to identify sensory difficulties and how to respond quickly and appropriately to them. These include children who have mild to severe visual or hearing impairment and a few children who are registered blind or deaf.
Includes bibliographical references (p. 95).
Keywords: Children, Blind -- Education (Early childhood); Hearing impaired children -- Education (Early childhood); Special education -- Activity programs; Education